Leber’s hereditary optic neuropathy – Molecular study of 540 Portuguese patients - Esteves, Sofia (2013)
Leber's hereditary optic neuropathy (LHON) is a maternal hereditary disease that causes blindness due to optic atrophy, with typical onset during the second or third decade of life and affects predominantly males. The primary etiological factor relates to mutations in the mitochondrial genome. The purposes of this study were the screening of the most common mutations associated with LHON by PCR-RFLP (G11778A, G3460A, G15257A, and T14484A) in 540 Portuguese patients, the sequencing of MT-ND1 and MT-ND6 genes, considered as hot spot for LHON mutations by direct sequencing of PCR products and the establishment of genotypephenotype correlation in the characterized patients. Of the 540 patients studied, 30 harbor three of the most common mutations investigated and in other seven patients we found seven pathogenic mutations, two of them present in MTND1 gene (G3688C and A4123G) and not described in the literature. In the approach taken to patients studied with LHON phenotype it was possible to perform a genotype-phenotype correlation in 6.9% of cases and only 5.5% had the most common mutations, while 1.4% presented other mitochondrial DNA (mtDNA)mutations between which, two not yet described in the literature. In addition to the mutations found, were also identified several polymorphisms, which reflect the high variability of mtDNA. This study also underlines the importance of further clinical and biochemical data of the patients to better clarify the pathology and thus provide a more accurate and precise diagnosis in addition to a more targeted molecular study.